Eosinophilic oesophagitis: relationship of quality of life with clinical, endoscopic and histological activity. Issue 8 (14th August 2015) - Safroneeva, E.; Coslovsky, M.; Kuehni, C. E.; Zwahlen, M.; Haas, N. A.; Panczak, R.; Taft, T. H.; Hirano, I.; Dellon, E. S.; Gonsalves, N.; Leung, J.; Bussmann, C.; et al.
Summary: Background: Knowledge about determinants of quality of life (QoL) in eosinophilic oesophagitis (EoO) patients helps to identify patients at risk of experiencing poor QoL and to tailor therapeutic interventions accordingly. Aim: To evaluate the impact of symptom severity, endoscopic and histological activity on EoE‐specific QoL in adult EoE patients. Methods: Ninety‐eight adult EoE patients were prospectively included (64% male, median age 39 years). Patients completed two validated instruments to assess EoE‐specific QoL (EoO‐QoL‐A) and symptom severity (adult EoE activity index patient‐reported outcome) and then underwent esophagogastroduodenoscopy with biopsy sampling. Physicians reported standardised information on EoE‐associated endoscopic and histological alterations. The Spearman's rank correlation coefficient was calculated to determine the relationship between QoL and symptom severity. Linear regression and analysis of variance was used to quantify the extent to which variations in severity of EoE symptoms, endoscopic and histological findings explain variations in QoL. Results: Quality of life strongly correlated with symptom severity ( r  = 0.610, P  <   0.001). While the variation in severity of symptoms, endoscopic and histological findings alone explained 38%, 35% and 22% of the variability in EoE‐related QoL, respectively, these together explained 60% of variation. Symptom severity explained 18–35% of the variation in each of the five QoL subscale scores. Conclusions: Eosinophilic oesophagitis symptom severity and biological disease activity determine QoL in adult patients with eosinophilic oesophagitis. Therefore, reduction in both eosinophilic oesophagitis symptoms as well as biological disease activity is essential for improvement of QoL in adult patients.Clinicaltrials.gov number, NCT00939263.